Вектор переноса энергии при поперечных смещениях упругой среды - Ванин, Виктор Антонович; Григорьев, А. А. (НТУ "ХПИ", 2010)
На основі аналогії рівнянь лінійної теорії пружності і електромагнітного поля виконане узагальнення теореми Умова – Пойтінга і отримана формула для вектора переносу енергії при поперечних зсувах пружного середовища. Представлена нова модель активного механічного середовища та вивчені особливості переносу енергії в гвинтовій хвилі трансляції, що рухається по ньому.

On the basis of the analogy of the equation of the linear theory of elasticity and an electromagnetic field the Poyting’s theorem generalization is executed and the formula for the vector of transferring the energy at a cross – section displacement of the elastic environment is obtained. A new model of an active mechanical environment is presented and the singularities of the transferring the energy in a spiral repeater wave which in its turn spreads along this environment are examined.
Keywords: линейная теория упругости; электромагнитные поля; перенос энергии; упругие среды; винтовые фононы; энергетический обмен